2013
DOI: 10.1074/jbc.m112.438341
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Promotes Protein Degradation of Epithelial Protein Lost in Neoplasm (EPLIN), a Putative Metastasis Suppressor, during Epithelial-mesenchymal Transition

Abstract: Background:The mechanism of EGF signaling in the regulation of prostate cancer (PCa) metastasis remains unclear. Results: EGF promotes epithelial-mesenchymal transition (EMT) and induces degradation of epithelial protein lost in neoplasm (EPLIN), a putative suppressor of PCa metastasis. Conclusion: EGF activates ERK1/2-dependent phosphorylation, ubiquitination, and protein turnover of EPLIN. Significance: This study suggested that blockade of EGF signaling could retard EMT and inhibit invasiveness of PCa cells. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 48 publications
2
35
0
Order By: Relevance
“…S2R and S in the supplemental material), such as the interferon pathway (57)(58)(59), the tumor necrosis factor (TNF) pathway (60), and growth factors such as the EGF pathway (61). Thus, PMA induction of the PKCs operates via key inflammatory processes previously shown to induce EMT (62)(63)(64)(65) and cooperates with the TGF-␤ pathway.…”
Section: Resultsmentioning
confidence: 99%
“…S2R and S in the supplemental material), such as the interferon pathway (57)(58)(59), the tumor necrosis factor (TNF) pathway (60), and growth factors such as the EGF pathway (61). Thus, PMA induction of the PKCs operates via key inflammatory processes previously shown to induce EMT (62)(63)(64)(65) and cooperates with the TGF-␤ pathway.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that the HCC with multiple observed lesions had more serious problems in protein degradation disorder. Although, the disturbance of protein degradation has been reported to be closely associated with different cancer types [40][41][42][43], the underlying mechanisms of the disturbance of UBC signaling pathway, which only occurred in HCC with multiple observed lesions, are not clear and need further investigation. On the other hand, the ERK signaling pathway is only enriched in the HCC with a single lesion, but it is normally regulated in HCC with multiple lesions; ERK signals were well known as an extremely important regulator of cell growth and proliferation.…”
Section: Ipa Network Analysis Of the Differentially Expressed Proteinsmentioning
confidence: 93%
“…EGF induced EMT was found to be mainly dependent on Akt activation, as inhibition of Akt signaling abolished EGF driven EMT in PCa cell lines [62, 63]. In addition, EGF was shown to selectively induce the protein degradation of epithelial origins in neoplasm; or LIM domain and actin binding 1, LIMA-1 (EPLIN), a putative suppressor of EMT in PCa [64]. Further mechanistic analysis revealed that EGF activated the phosphorylation, ubiquitination, and degradation of EPLIN through an extracellular signal-regulated kinase 1/2 (ERK1/2)-dependent signaling cascade.…”
Section: Molecular Mechanisms Of Emt Induction In Pcamentioning
confidence: 99%